Perbedaan Kebutuhan Nitrogen untuk Produksi Kedelai di Tanah Mineral dan Mineral Bergambut Dengan Budidaya Jenuh Air - -, Bachtiar; Ghulamahdi, Munif; Melati, Maya; Guntoro, Dwi; Sutandi, Atang (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Development of soybean (Glycine max (L) Merr.) in tidal land are faced with problems physical, chemical and biological soil properties, such as high organic matter, high soil acidity, toxicity of Fe and Al, and deficiency of nutrients N, P , K, Ca and Mg. N content is high (> 0.51%) but with low availability.  The research objective is to determine the dose and timing of N, P and K application in accordance with the needs of soybean plants to have optimally growth and production in mineral and peaty mineral soil in tidal land. The research was conducted in mineral and peaty mineral soil of tidal land type C and B, District of Tanjung Lago, Banyuasin Regency, Province of South Sumatra from April to August 2014. The model is linear using split plots in a randomized block design. Varieties of Willis and Tanggamus were used for nitrogen application experiment.  The time of fertilizer application is at 2, 3 and 4 weeks after planting (WAP), 2, 3, 4 and 5 WAP, and 2, 3, 4, 5 and 6 WAP. The concentration of nitrogen is 7,5; 10; 12,5 and 15 g/l water with spraying volume of 400 l/ha.  In the mineral soil, dry weight of nodules and Willis biomass increased with increasing frequency time of fertilization, otherwise Tanggamus more fluctuating and declined at higher frequency of fertilization. Wilis variety generating the highest production of 3,5 ton/ha.  In the peaty mineral soil, dry weight of nodules and biomass were not significant.  Willis productivity tends to decrease with increasing nitrogen concentrations.  Tanggamus productivity tends to increase with increasing nitrogen concentration at all level of time fertilization.  Tanggamus tend to generate higher productivity of 3,2 ton/ha.